WEB-BASED STUDENT PRESENCE INFORMATION SYSTEM DESIGN AT SDIT IBNU KHALDUN PANAMBANGAN CIREBON - Sukma Hendrian (Green Publisher, 2022)
The attendance system at SDIT Ibnu Khaldun Panambangan Cirebon previously still used the manual method of inputting attendance and there was no system to be able to provide attendance information to parents. This study aims to create a website-based student attendance information system at SDIT Ibnu Khaldun Panambangan Cirebon. Website-based student attendance information is an effective, fast, and accurate means of delivery, making it easier for schools, especially in providing student attendance information services to parents. Making a website-based student attendance system begins by analyzing system requirements, namely by direct interviews with prospective users and making system designs to the results of the system. Admin or teacher in charge of inputting student attendance. The system can recap each period or adjust the date that the system wants to set. System testing with Black Box testing as a functional feasibility test. The results of this research are the application of this student attendance system can facilitate the work of teachers in inputting attendance, make it easier for teachers to recapitulate student attendance, make it easier for the school to convey information to parents about student attendance at school, and make it easier for parents to get attendance reports. learners.